Determinants of Maternal Behavior in Basic Immunization of Children Aged 0-9 Months at Health Center in Southern Nias District 2023 - Sri Lestari Ramadhani Nasution; Reynel Putri Pratiwi Wau; Wika Hanida (Postgraduate, University of Mataram, 2023)
The aim of this research was to determine the influence of mothers' attitudes, knowledge and perceptions on the status of basic immunization requirements for children aged 0-9 months at the Community Health Center of South Nias Regency. This research uses a quantitative anaclitic research design with a cross sectional approach. The population in this study were parents who had children aged 0-9 months who were within the coverage area of ​​the South Nias Regency Health Center. The sample size used in this research is 120 samples. Data analysis in this research is univariate and bivariate analysis. The results obtained from this research are that mothers' attitudes, knowledge and perceptions partially influence the basic immunization status of children aged 0-9 months at the Community Health Center, South Nias Regency, P-value < 0.05. Attitudes, knowledge and perceptions simultaneously influence the basic immunization status of children aged 0-9 months at the Community Health Center of South Nias Regency P-value < 0.05.